Mesoporous Ni-P@NiCo2O4 composite materials for high performance aqueous asymmetric supercapacitors. (20th December 2016) - Li, Xudong; Ding, Rui; Yi, Lanhua; Shi, Wei; Xu, Qilei; Liu, Enhui
Highlights: Mesoporous Ni-P@NiCo2 O4 composite for supercapacitors was constructed. The Ni-P@NiCo2 O4 composite exhibits superior performance than the Ni-P and NiCo2 O4 . The AC//Ni-P@NiCo2 O4 capacitor outdoes the AC//Ni-P and AC//NiCo2 O4 capacitors. The superior behavior is due to the synergistic effect between Ni-P and NiCo2 O4 . Abstract: Mesoporous Ni-P@NiCo2 O4 composite materials have been fabricated via a facile strategy including solvothermal synthesis of Ni-P and subsequent chemical deposition of NiCo2 O4 . Due to the synergistic effect between Ni-P and NiCo2 O4, the Ni-P@NiCo2 O4 composite materials exhibit an enhanced performance (1240 F g −1 at 1 A g −1, 668 F g −1 at 16 A g −1 ) compared with the bare Ni-P materials (717 F g −1 at 1 A g −1, 106 F g −1 at 16 A g −1 ) and NiCo2 O4 materials (741 F g −1 at 1 A g −1, 457 F g −1 at 16 A g −1 ). Furthermore, the AC//Ni-P@NiCo2 O4 asymmetric capacitor exhibits superior energy/power densities (13.3 Wh kg −1 /5.7 kW kg −1 ) and cycling behavior (78.3% retention after 10, 000 cycles at 4 A g −1 ) than the AC//Ni-P asymmetric capacitor (7.4 Wh kg −1 /5.7 kW kg −1, 63.4% retention after 10, 000 cycles at 4 A g −1 ) and AC//NiCo2 O4 asymmetric capacitor (10.4 Wh kg −1 /5.6 kW kg −1, 32.4% retention after 10, 000 cycles at 4 A g −1 ). The high performance makes the mesoporous Ni-P@NiCo2 O4 composite materials promising electrode materials for supercapacitors.